Here Today, Gone Tomorrow? Mapping and modeling the pop-up retail customer journey. (May 2020) - Rudkowski, Janice; Heney, Chelsea; Yu, Hong; Sedlezky, Sean; Gunn, Frances
Abstract: Pop-up retail and customer journey mapping are widely adopted in the retail industry, yet they have received modest coverage within academic literature to date. Through a qualitative field study of five marketplace-based pop-ups (MBPUs), this research defines and identifies differences and similarities between marketplace-based pop-ups (MBPUs) and brand-based pop-ups (BBPUs), seeks to understand how marketplace-based pop-ups fit within the customer journey and experience, and explores how touchpoint ownership and influence illuminates the understanding of the marketplace-based pop-up customer journey. Further, this research extends an existing conceptual customer journey framework to visually map and model the purchase stages, touchpoint categories and types of marketplace-based pop-up customer journeys. As a result, this research presents and discusses three emerging themes (here today gone tomorrow; high-touch low-tech; and ownership and influence) to further the understanding of MBPUs. Pop-ups are more than a single encounter; they are a complex customer journey process, whereby the customer travels through pre-purchase, purchase and post-purchase stages, and across multiple touchpoints.